Mediating spoken meaning-making in genre-based lessons: The role of metalinguistic concepts. (February 2021) - Herazo, José David
Abstract: This study describes how an 11-year old learner developed the metalinguistic concept of tenor during genre-based lessons in shopping exchanges and recipes and how such concept mediated the learner's spoken meaning-making in a second language (L2). The study adopts a sociocultural perspective according to which metalinguistic terms are part of a system of abstract conceptual knowledge describing how the L2 works. The study draws on data from a larger investigation involving lesson observations, a teacher reflection log, and lesson artifacts during two curricular units spanning four months. Genetic analysis of the learner's use of the concept of tenor in classroom interaction revealed that this concept evolved as a pairing of awareness of context and related L2 choice in the genres that were focus of instruction, becoming also available during an extension task after instruction. In turn, systemic-functional linguistic analysis of the learner's spoken texts showed her development of the concept was paired by an increasing control of spoken L2 meaning-making. The study underscores that metalanguage served as a conceptual tool that mediated the learner's spoken discourse during and after genre-based lessons, transforming the learner's approach to spoken L2 meaning-making.